Partnership pathways associated with lifetime childlessness in Belgium and Finland - Rees, Alice; Schnor, Christine; Jalovaara, Marika (Society of Social and Economic Research in the Universities of Turku, 2026)
In recent decades, many European countries have witnessed both a rise in ultimate childlessness and
increasing diversity in partnership trajectories. This paper investigates patterns of partnership trajectories
associated with childlessness in Belgium and Finland from a life-course perspective. Using sequence
and cluster analysis on register data, we examine the partnership histories of Belgian (N=19,590) and
Finnish (N=13,368) men and women born in 1975, following them from age 18 to 45. We identified five
typical partnership clusters among the Belgian childless and four among the Finnish. Three clusters—
Never Partnered, Partnership Instability, and Marriage—are common to both countries. Most childless
individuals in both countries remain unpartnered or face partnership instability. A turbulence index was
then computed to assess the difference of turbulence of the sequences between the two countries. This paper
contributes to the literature on childlessness by examining the heterogeneity of partnership biographies
and cross-country differences using high-quality administrative data.